Graha Sastra Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Neni Meilani Damanik; Ratna Amanati; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Literature as an art and culture can be used to convey many forms of messages like moral, religion and cultural values that can affect the mindset of society. As time goes by, the art of literature started neglected. This is cause a certain anxiety of the existence of literary art in the future. Related to this issue, Pekanbaru needs The Graha Sastra facilities which can serve as a space and a media appreciation of the literary art. To achieve this goal, Graha Sastra was designed with facilities that can support the literary arts development activities such as education, production and recreation facilities. "Architecture as a language of literature" was appointed as Graha Literature’s design concept. This concept was implemented in the outer space order, mass formation, and the space order in the buildings. Postmodern Architecture approach with emphasis on hybrid method, the design of the Graha Sastra is expected can produce an architectural design which appropriate, either to the building or the enthusiasts of the literary art. Elements of the Graha Satra in Pekanbaru design consist of the zoning area, mass order, the mass formation,outdoor space, structure, space order in buildings and facade. Design patterns at Graha Sastra using design patterns that correspond to the elements of literature and combined two characters style, realism and romanticism. Whereas the application of the concept can be felt at the momentwhen the user reach the recreational facilities through a spinning and contoured circulation as well as stages of the plot of the flow of a story.Keywords: Languange, Literary Elements, Hybrid Architecture